Rewitalizacja jako obszar współpracy międzysektorowej = Revitalization as a field of cross-sectoral cooperation - Bazuń, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of a revitalization process is to bring down degraded areas from a state of crisis. This paper contains analysis of the cooperation of professionals representing various institutions, professions and sectors in the revitalization process. The text sets out what conditions should be fulfilled in order to make inter-sectoral cooperation contribute to achieving the key objectives of the revitalization process. The article contains information on the legal context of revitalization and optimal conditions for revitalization of crosssectoral cooperation.
Keywords: rewitalizacja; współpraca międzysektorowa; tereny miejskie; partycypacja; revitalization; cross-sectoral cooperation; urban areas; participations